2003
DOI: 10.1189/jlb.1002492
|View full text |Cite
|
Sign up to set email alerts
|

IgD-receptor (IgD-R) cross-linking partially protects murine T cells from dexamethasone-induced apoptosis

Abstract: Based on our previous findings that immunoglobulin D (IgD) receptor (IgD-R) cross-linking with oligomeric IgD (IgD-R-xL) led to T cell activation, we examined the effect of IgD-R-xL on the expression of Fas antigen and apoptosis induction. In splenic T cells, IgD-R-xL followed by dexamethasone (dex) treatment resulted in a decreased percentage of Fas-positive cells as well as a decreased mean fluorescence intensity (P<0.05) when compared with cells treated with dex alone. There are significant differences in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The studies of interaction of secreted IgD with T cells postulated a putative IgD receptor on a small fraction of T cells in human peripheral blood and mouse peripheral lymphoid organs, which binds to N‐linked carbohydrate moieties of IgD (67, 68). Crosslinking of IgD receptor on T cells was shown to protect T cells from apoptosis (69). It has also been shown that this IgD receptor could promote the formation of immune synapse between cognate T cells and naive B cells that express transmembrane IgD and thereby augment antigen presentation and antibody production (70, 71).…”
Section: Distribution Of Igd In Humansmentioning
confidence: 99%
“…The studies of interaction of secreted IgD with T cells postulated a putative IgD receptor on a small fraction of T cells in human peripheral blood and mouse peripheral lymphoid organs, which binds to N‐linked carbohydrate moieties of IgD (67, 68). Crosslinking of IgD receptor on T cells was shown to protect T cells from apoptosis (69). It has also been shown that this IgD receptor could promote the formation of immune synapse between cognate T cells and naive B cells that express transmembrane IgD and thereby augment antigen presentation and antibody production (70, 71).…”
Section: Distribution Of Igd In Humansmentioning
confidence: 99%
“…However, cellassociated IgD includes transmembrane IgD, intracellular IgD, and secreted IgD bound to various cell types. Crosslinking of IgD receptor on T cells was shown to protect T cells from apoptosis (Tamma and Coico 2003). It has also been shown that this IgD receptor could promote the formation of immune synapse between cognate T cells and naïve B cells that express transmembrane IgD and thereby boost antigen presentation and antibody production (Wu et al 1999;Tamma et al 2001).…”
Section: Discovery Of Igdmentioning
confidence: 99%
“…Crosslinking of surface-bound IgD on basophils by anti-IgD antibodies induces calcium influx, the secretion of B cell activating cytokines, and the release of antimicrobial factors (Chen et al, 2009;Sechet et al, 2003). Oligomeric IgD can activate T cells, while partially preventing B cells from corticosteroid-induced apoptosis (Lakshmi Tamma et al, 2001;Tamma and Coico, 2003;Wu et al, 1999). There is evidence that IgD binds to respiratory bacteria and their products (Chen et al, 2009; Forsgren and Grubb, 1979;Samuelsson et al, 2007).…”
Section: Introductionmentioning
confidence: 95%